Gender Differences in Creative Perceptions of Undergraduate Students - Naderi, Habibollah; Abdullah, Rohani; Tengku Abdul Hamid, Tengku Aizan; Jamaluddin, Sharir; Mallan, Vijay Kumar (2009)

(untitled)
This study investigated the difference between gender-role identity and creativity of students at Malaysian Universities. The respondents were 153 undergraduate Iranian students (48 females, 105 males; aged 19 to 27 years) in Malaysia Universities. All students were given a Khatena-Torrance Creative Perception Inventory Test (KTCPI). The instrument comprised two subscales, namely, Something About Myself (SAM) and What Kind of Person Are You (WKOPAY)? Each subscale had fifty items. The results revealed no significant difference between female and male students` overall creative perception. Further examination revealed that male students score higher in the WKOPAY subscale (t = 2.578, p = 0.011), while females scored higher than males in the initiative factor (t = 3.566, p = 0.000) and males scored higher than females in the environmental sensitivity factor (t = -2.216, p = 0.028) in the SAM subscale. Further replications on similar samples are needed.